2011
DOI: 10.1074/jbc.m110.182600
|View full text |Cite
|
Sign up to set email alerts
|

Triheteromeric NR1/NR2A/NR2B Receptors Constitute the Major N-Methyl-d-aspartate Receptor Population in Adult Hippocampal Synapses

Abstract: NMDA receptors (NMDARs), fundamental to learning and memory and implicated in certain neurological disorders, are heterotetrameric complexes composed of two NR1 and two NR2 subunits. The function of synaptic NMDARs in postnatal principal forebrain neurons is typically attributed to diheteromeric NR1/NR2A and NR1/NR2B receptors, despite compelling evidence for triheteromeric NR1/NR2A/NR2B receptors. In synapses, the properties of triheteromeric NMDARs could thus far not be distinguished from those of mixtures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
209
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(227 citation statements)
references
References 65 publications
10
209
0
Order By: Relevance
“…The most parsimonious explanation of these data is that postsynaptic receptors at BLA excitatory synapses are largely GluN1/GluN2A/GluN2B heterotrimers. Interestingly, a similar conclusion has recently been reached for excitatory synapses on mature hippocampal pyramidal neurons (Rauner and Kohr 2011), where the properties of NMDA receptor-mediated EPSCs share the same kinetic and pharmacological properties as those in BLA neurons .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The most parsimonious explanation of these data is that postsynaptic receptors at BLA excitatory synapses are largely GluN1/GluN2A/GluN2B heterotrimers. Interestingly, a similar conclusion has recently been reached for excitatory synapses on mature hippocampal pyramidal neurons (Rauner and Kohr 2011), where the properties of NMDA receptor-mediated EPSCs share the same kinetic and pharmacological properties as those in BLA neurons .…”
Section: Discussionmentioning
confidence: 64%
“…Both GluN2A and GluN2B subunits are present in the basolateral amygdala (BLA) (Farb and LeDoux 1997;Lopez de Armentia and Sah 2003), and pharmacological studies have suggested that amygdala-dependent learning requires the activation of GluN1/GluN2B heterodimers (Rodrigues et al 2001;Walker and Davis 2008). However, although GluN2B subunits are present at synapses, whether they assemble as heterodimers or heterotrimers is not clear Rauner and Kohr 2011). In this study, we investigated the subunit composition of synaptic NMDA receptors at glutamatergic synapses on principal neurons in the BLA.…”
mentioning
confidence: 99%
“…By contrast, some highly subunit-selective negative allosteric modulators are less effective inhibitors of triheteromeric GluN1/2A/2B receptors and therefore primarily inhibit either GluN1/2A or GluN1/2B receptors [e.g., TCN-201 or ifenprodil, respectively (20,45)]. Both subunit selectivity and mechanism of action are therefore important considerations for the application of a pharmacological tool compound in neurophysiological studies, because many central synapses in the adult hippocampus and cortex contain a mixed population of GluN1/2A, GluN1/2B, and triheteromeric GluN1/2A/2B receptors (31).…”
Section: Discussionmentioning
confidence: 99%
“…3C). However, a competitive antagonist with 100-fold selectivity for GluN1/2A over GluN1/2B is still expected to produce robust inhibition of triheteromeric GluN1/2A/2B receptors, which are the primary GluN2B-containing NMDA receptors in the adult hippocampus and cortex (31)(32)(33).…”
Section: Significancementioning
confidence: 99%
“…Among these, NMDAR has been the center of attention predominantly due to its unique features: 1) it allows Ca 2+ influx upon activation, in addition to other cation-mediated currents, and 2) it requires additional conditions for activation (specifically, the Mg 2+ block has to be released for opening) (MacDermott et al, 1986;McBain and Mayer, 1994;Regehr and Tank, 1990). The combination of 2 duplicated subunits (generally, GluN1 subunits with co-activator, glycine binding sites, and regulatory GluN2 subunits with glutamate binding sites) consist of NMDARs, and the subunit composition (particularly among GluN2 isoforms) is known to determine ion conductance through the receptor and be developmentally regulated (Al-Hallaq et al, 2007;Collingridge et al, 2009;Monyer et al, 1994;Rauner and Kohr, 2011;Sheng et al, 1994;Stocca and Vicini, 1998). The mature human brain is known to express mainly GluN1 and GluN2A (Petralia et al, 1994).…”
Section: Traditional Understanding Of Nmda Receptorsmentioning
confidence: 99%